The influence of range‐wide plant genetic variation on soil invertebrate communities. Issue 7 (23rd November 2017) - Fitzpatrick, Connor R.; Mikhailitchenko, Anna V.; Anstett, Daniel N.; Johnson, Marc T. J.
Abstract : Plant genetic variation can have far‐reaching effects on associated communities and ecosystems. Heritable variation in ecologically relevant plant traits is often non‐randomly distributed across a species' range and can exhibit geographic clines. In the event of range expansions and migration, previously unfamiliar genotypes may have large impacts on resident communities and ecosystems due to the introduction of novel and heritable phenotypic variation. Here we test the hypothesis that geographic origin of a focal plant genotype has effects on belowground invertebrate communities using a common garden field experiment. We sampled soil invertebrates from 103 Oenothera biennis genotypes, which were collected from across the species' range and planted into a common garden field experiment at the northern range limit. We enumerated 24 000 individuals from 190 morphospecies and found that the diversity, abundance, and composition of soil invertebrate communities varied greatly among plant genotypes. Despite strong effects of plant genotype, we found few genetic correlations between plant traits and soil invertebrate community variables. However, herbivore damage was strongly related to variation in the soil invertebrate community. Geographic origin of plant genotypes had at most a weak effect on belowground communities. We speculate that predicting the extended effects of population movement on associated communities will require detailed knowledge of the trait variation occurring within focal species across particular environmental gradients.